Periodic table in the style of a zigzag (James Emerson Reynolds, 1886) - Reynolds, James Emerson; Mazurs, Edward G. (1886)
Graphic representation of the periodic table of chemical elements in the style of a zigzag. This table was originated by Irish chemist James Emerson Reynolds (1844-1920) in 1886 and and classified by Mazurs as Type IIC1-2 in his seminal work Types of Graphic Representation of the Periodic System of Chemical Elements (1957). This illustration appears as Figure 44 on page 119 of Mazurs' 1957 publication.
Keywords: Scientific illustration; Periodic table of the elements; Periodic law; Chemical elements